Development of video mind mapping-based teaching materials on relations and functions to increase junior high school students' learning motivation - Rohimatunnisa, Dela; Nurhikmayati, Iik (UNION : Jurnal Ilmiah Pendidikan Matematika, 2024)
This study aims to produce teaching materials based on video mind mapping on relations and functions to increase student learning motivation. The research is a type of Research and Development (R&D) using the ADDIE development model but is only limited to the Development stage. The research instruments used in this study were validation sheets, test questions, and interviews. The subjects of this study were three students of class VIII at MTsN 1 Majalengka with high, medium, and low ability levels. The results indicate that the developed video mind mapping-based teaching materials have met valid criteria, making them suitable as alternative teaching materials to increase student learning motivation. The implementation of video mind mapping-based teaching materials shows promise in enhancing students' motivation to learn relations and functions, suggesting potential broader application in educational settings.